April love [videorecording (DVD)] - Miller, Winston, 1910-1994; Boone, Pat; Jones, Shirley, 1934 March 31-; Michaels, Dolores, 1933-2001; O'Connell, Arthur, 1908-1981; Crowley, Matt, 1904-1983; Nolan, Jeanette, 1911-1998; Jackson, Brad; Cline, Wilfred M.; Newman, Alfred, 1901-1970; Mockridge, Cyril J. (Cyril John), 1896-1979; Webster, Paul Francis; et al. (20th Century Fox cinema archives., 2013)
The story of a young man sent to his uncle's farm to rehabilitate himself, how he adapts to his new surroundings and falls in love.